Tympanoplastik Typ I im frühen Kindesalter erfolgsversprechend - Volkenstein, Stefan (Laryngo-Rhino-Otologie, 2018)
Singh GB et al. Paediatric tympanoplasty: comparative study between patients aged 5–8 years and those aged over 14 years. J Laryngol Otol 2016; 130: 635–639